Biorreator wave como alternativa para expansão de células estromais mesenquimais - Silva, Juliana de Sá da (2015)
Mesenchymal stromal cells (MSCs) are required by the scientific community in the development and enhancement of therapeutic techniques in different fields of medicine. The MSCs are present in small concentrations in tissues, which makes necessary the expansion in vitro for enable studies and therapeutic applicability. These are cells with high sensitivity to environmental conditions of cultivation. So, for increase productivity in vitro is used the technology of bioreactors in the development of processes in order to produce high cell densities in less time, with reduce use of resources and maintaining a safe operation. The new concepts of "disposable bioreactors", as the wave-induced motion bioreactor or Wave bioreactor, with possibility operating in a closed system, controlled and automated, reduced investment cost and operation, less risk of contamination, higher level biosecurity, added to the fact of being a underexplored technology and already approved by the FDA (Food and Drugs Administration) becomes a highly attractive alternative bioprocessing for cultivation of animal cells in large scale. In this context, the present work aims to develop a protocol for cultivation of MSCs in the Wave Bioreactor System 2/10. Experiments were performed to characterize the CEMs's culture behavior in the Wave bioreactor to obtain high cell productivity while maintaining the therapeutic potential of the CEMs. The experiments were carried out with 2 L Cellbag and Cultispher-S microcarrier with 300 ml of α-MEM medium culture supplemented with glucose, glutamine, and arginine and 15% v/v fetal bovine serum at 37 ° C and pH between 6,9-7,4. In the preliminary experiments it was verified that most of the inoculated cells did not adhere to the microcarriers. It was shown that such behavior is due to low relation between adhesion area (AMC = total projected area of the microcarriers) and wet surface area of Cellbag (ASMCellbag), which in the normal condition of operation results an adhesion between 25,7 and 61,7% of the inoculated cells. To solve the problem were performed experiments reducing ACellbag which enabled improvements in cell adhesion by up to 100%. It was also found low performance of the cell expansion phase, presumably linked to operational problems like: microcarriers segregation in certain regions of the bioreactor causing depletion of nutrients, formation of aggregates of MCs colonized with cells and adhesion of MCs to Cellbag. In addition, it was observed that reducing CEM/MC ratio at the start of the culture, the cell expansion factor could be increased to values equal to or greater than 10. These results show that the Wave bioreactor has good potential for expansion of MSCs and that the same can be improved.